BCMA CAR-T therapy as salvage therapy in patients with plasmablastic myeloma - Chengwei Jin; Jing Deng; Ying Jiang; Jun Zhu; Liqing Kang; Su Li (Hematology)
Objectives: Plasmablastic myeloma (PBM) is a variant of multiple myeloma associated with a poor prognosis. We investigated the efficacy and safety of B-cell maturation antigen (BCMA) chimeric antigen receptor T cell (CAR-T) therapy in patients with PBM.Methods: The study comprised six patients diagnosed with PBM between January 1, 2023 and December 31, 2023. The patients received BCMA single-target CAR-T therapy or BMCA/CD19 dual-target CAR-T therapy, with some patients undergoing hematopoietic stem cell transplantation before treatment. The median patient age was 55.5 years (range, 41–63). Four patients exhibited high-risk cytogenetic abnormalities.Results: The objective response rate (ORR) was 83.3%, with four of six patients achieving a complete response or better and three of six achieving a strigent complete response. Two patients exhibited progression-free survival (PFS) of at least 6 months, one of whom succumbed to a pulmonary infection, whereas four patients died of disease progression. Cytokine release syndrome (CRS) was observed in all patients, three of whom experienced grade 3–4 CRS. Two patients experienced grade 1–2 immune effector cell-associated neurotoxicity syndrome. There were no CRS-related deaths.Conclusion: BCMA CAR-T therapy was safe and effective as a salvage treatment for PBM, and its toxicity was controllable. Future research will examine the use of CAR-T therapy as part of combination regimens.